Violence Against Children in the Novel 'Misteri Bilik Korek Api' by Ruwi Meita - Puteri Najlah Meylani (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study is driven by the dual objectives of comprehensively identifying and elucidating the diverse manifestations of violence against children within Ruwi Meita's novel "Misteri Bilik Korek Api" (The Mystery of the Matchbox Room).The selection of the theme of violence stems from the novel's portrayal of acts of violence directed towards children. To undertake a comprehensive analysis of these instances, this research employs a literary psychology approach, augmented by the conceptual framework provided by Azevedo and Viviane's typology of five distinct forms of violence. Employing a qualitative methodology, the study delves into the intricate fabric of the prose, facilitating an in-depth exploration and interpretation of the textual data. The outcomes of this inquiry illuminate five primary forms of violence that children undergo within the novel's narrative canvas: Indifference: Evidencing scenarios in which characters display an unsettling apathy towards the well-being of children. Contempt: Unveiling instances of disdain or disrespect aimed at children from other characters. Isolation: Illuminating instances where children are deliberately secluded or isolated from their social milieu. Rejection: Disclosing portrayals of children confronting exclusion or repudiation across various spheres of their existence. Terror: Exposing moments of intense fear and apprehension experienced by children as a result of threatening circumstances or actions.